2021
DOI: 10.3389/fneur.2021.673893
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning and Care Coordination for People With Parkinson's Disease and Their Family Caregivers—Study Protocol for a Multicentre, Randomized Controlled Trial

Abstract: Background: Parkinson's disease (PD) is a progressive neurodegenerative disease with motor- and non-motor symptoms. When the disease progresses, symptom burden increases. Consequently, additional care demands develop, the complexity of treatment increases, and the patient's quality of life is progressively threatened. To address these challenges, there is growing awareness of the potential benefits of palliative care for people with PD. This includes communication about end-of-life issues, such as Advance Care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Indeed, one of the outcomes in PD_Pal is the percentage of patients with documented ACP decisions at a 6-month follow-up. Secondary endpoints include caregivers’ and patients’ QoL, perceived care coordination, symptoms management, and reduced patient symptom burden as well as cost-effectiveness [ 49 ]. The ultimate goal of the project is to provide a model that is feasible, cost-effective, and can inform new guidelines about the timing and referral for ACP.…”
Section: Home Care For Late-stage Pdmentioning
confidence: 99%
“…Indeed, one of the outcomes in PD_Pal is the percentage of patients with documented ACP decisions at a 6-month follow-up. Secondary endpoints include caregivers’ and patients’ QoL, perceived care coordination, symptoms management, and reduced patient symptom burden as well as cost-effectiveness [ 49 ]. The ultimate goal of the project is to provide a model that is feasible, cost-effective, and can inform new guidelines about the timing and referral for ACP.…”
Section: Home Care For Late-stage Pdmentioning
confidence: 99%
“…Unfortunately, concepts for other progressive neurological diseases are rare (Oliver et al 2020 ). In a recent international multicenter study, concepts for palliative care interventions were studied and palliative care training programs were developed (Gatsios et al 2021 ; Meinders et al 2021 ). A survey on aPS patients revealed that this patient group prefers an early conversation about diagnosis with information about the disease, natural history, prognosis, and treatment options (Saranza et al 2021 ).…”
Section: Clinical Care For Patients With Parkinson’s Disease and Atyp...mentioning
confidence: 99%